Pola Gradien Temperatur Bawah Permukaan Dangkal Manifestasi Panas Bumi Desa Noongan Tiga Kabupaten Minahasa - Bethrany F. Landung; Donny R. Wenas; Jeilen G. N. Nusa; Cyrke A. N. Bujung (Jurnal FisTa : Fisika dan Terapannya, 2022)
Geothermal is one of the natural resources that has great potential to be used as a renewable energy. The existence of geothermal resource on the surface is reflected by the presence of the geothermal manifestations on earth surface. This research was conducted to map the shallow subsurface temperature and determine the temperature gradient pattern of the geothermal manifestation in Noongan Tiga Village, Minahasa. This research uses observation method by measuring the temperature at the depth of 3 cm, 9 cm, and 15 cm in the morning, daytime, and the afternoon at 10 different points. The results showed that in that in the morning the temperature average reached 42,03 0C at the depth of 3 cm, 50,09 0C at the depth of 9 cm, and 60,26 0C at the depth of 15 cm. In the daytime, the temperature average rises to 59,2 0C at the depth of 3 cm, 66,01 0C at the depth of 9 cm, and 76,16 0C at the depth of 15 cm. While in the afternoon the temperature average reaching 41,28 0C at the depth of 3 cm, 49,46 0C at the depth of 9 cm, and 59,38 0C at the depth of 15 cm. The temperature gradient obtained shows an increase in temperature where the deeper you go, the temperature increases, with a linear temperature gradient pattern to the northeast.